(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Traditional transactional banking in India is being replaced by Relationship Marketing. It’s clearfrom the tagline Client is King that every company situation revolves on making the customer happy. Inorder to better understand the customer’s wants and expectations, the CRM idea has been put into place,with the goal of establishing a long-term connection. In today’s business environment, banks’ successdepends on a variety of factors, including a commitment to individualized service, effective databasemanagement, a focus on building client loyalty, and effective retention measures. The purpose of thisarticle is to discuss the goals, methods, and advantages of e-CRM in the Indian banking industry.